A rapid and reliable method for early Legionella pneumophila identification and characterization in support of the epidemiology study - Monistero, Valentina; Vicari, Nadia; Prati, Paola; Bragoni, Roldano; Gazzola, Alessandra; Sala, Lorenza; Maisano, Antonio; Moroni, Paolo; Bronzo, Valerio; Luini, Mario Vittorio; Castiglioni, Bianca; Cremonesi, Paola (Frontiers in Microbiology, 2024)
Legionnaires' disease is a severe pneumonia predominantly caused by Legionella pneumophila (Lp), whose major reservoir are artificial water systems. As most human infections are caused by L. pneumophila serogroup 1 (Lp1), a reliable method for Lp distinction can be crucial for bacterial spread prevention. As the ability to withstand in environments and to cause the waterborne disease is strongly related to specific genes, the identification of virulent strains can be of great relevance to implement water environmental monitoring and to contain harmful outbreaks to public health. We aimed to test an assay for Lp identification among different Legionella species, and to determine the serogroups.Additionally, we investigated the carriage of virulence and antimicrobial resistance genes. A total of 90 Legionella spp. isolates identified by phenotypic tests were subjected to the designed quantitative PCR assay targeting specific mip for Lp, wzm for serogroup 1, pvcA and ahpD for biofilm production.Eleven serogroups were investigated in all our isolates tested positive for mip gene, subsequently analyzed for 12 virulence and 8 antimicrobial resistance genes. Only the 70 Lp isolates were positive for mip. Out of 27 Lp isolates belonging to serogroup 1 based on agglutination test, 23 (85.2%) carried wzm. The presence of ahpD and pvcA was found in 94.3% and 98.6% of Lp isolates, respectively. By multiplex PCR, all 23 wzm-positive strains were confirmed as serogroup 1 that was the most predominant (33%). At least one virulence gene was detected in all Lp isolates. The most frequent gene was ispE (100%), followed by issD (96%), icmK and enhC (93%), cpxA (91%), rtxA2 (74%), lvhB8-B9 (61%), and prpA (54%). The other genes were less diffused in Lp strains (rtxA1, 44%; lvhB3-B4, 47%; pvcB, 27%; lvrE, 24%). Of the macrolide resistance genes, the ereA was found in 84% of Lp strains, while only 14 (20%) harbored the lpeAB among the efflux pump genes. The assays validated in this study enable the simultaneous Lp and Lp1 detection. The differentiation of Lp strains according to their virulence properties could be useful to predict the bacterial ability to survive and to cause the disease.